Antimicrobial Activities and Mechanism of Action of Petiveria alliacea Stem Extract - Ika Kurnia Sukmawati; Jajang Jafar Sodik; Mulyani, Yani (Talenta Publisher, 2018)
Abstract. This research aimed to determine the antimicrobial activity of ethanol extract of Petiveria alliacea stem (EEPS) against Staphylococcus aureus, Pseudomonas aeruginosa, Escherichia coli, and Candida albicans. The minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) were determined by perforation and broth micro dilution methods. Study on the mechanism of action of EEPS was conducted by molecular docking and Scanning Electron Microscopy (SEM) techniques. The results showed that EEPS had an inhibitory activity against Staphylococcus aureus, Pseudomonas aeruginosa, Escherichia coli and Candida albicans with MIC values of 256, 128, 256, 512 Âµg/ml, consecutively. These values are included in to the medium category. Through the process of molecular docking, the best interaction was observed between S-benzyl-L-cysteine sulfoxide with penicillin-binding protein receptor of Pseudomonas aeruginosa characterized by free energy change (Î”G) of 4.32 kcal/mol, and the Ki value of 682.16 Î¼M. Four folds of MIC of the EEPS caused changes in the morphology of Pseudomonas aeruginosa. EEPS possessed antimicrobial activities against Staphylococcus aureus, Pseudomonas aeruginosa, Escherichia coli, and Candida albicans. Keywords: Antimicrobial Activity, Molecular Docking, Petiveria alliacea, SEM.